MANAJEMEN LAYANAN SISWA DALAM MENINGKATKAN PRESTASI NON AKADEMIK DI SEKOLAH DASAR - Andini, Faradilla; Fakhri, Jamal; Romlah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study evaluates the impact of student service management on improving non-academic achievement, with a focus on the aspects of planning, organizing, implementation, and supervision. The results from the planning phase show that well-designed service programs tailored to students' needs can facilitate the development of non-academic skills such as leadership, cooperation, and communication abilities. In the organizing phase, clear role distribution and collaboration between teachers, counselors, and school staff enhanced the program's effectiveness. The program implementation was optimal when participatory learning methods and diverse extracurricular activities were applied, which significantly increased student engagement. Consistent supervision and regular evaluations also played a critical role in ensuring the sustainability and continuous improvement of the services. Overall, well-executed student service management contributes to the enhancement of non-academic achievements, boosting students' confidence, social skills, and active participation